Suitability of drip automation systems for optimal irrigation scheduling - Manasa K (Department of irrigation and drainage engineering, Kelappaji college of agricultural engineering and technology, 2015)
Automation in irrigation management refers to those innovations which partially or fully replace manual intervention from watering operations. Automized irrigation includes automation at regional level or farm level. Recently, technological advances have been made in soil water sensors for efficient and automatic operation of irrigation system by which exact quantity of required water can be supplied to the crop. Automatic soil water sensor-based irrigation seeks to maintain a desired soil water range in the root zone that is optimal for plant growth.The present study was conducted to evaluate the suitability of drip automation systems for optimal irrigation scheduling. The field experiment was done in the rain shelter in the research plot of Nodal Water Technology Centre, College of Horticulture, Vellanikkara, during the months of October 2014–March 2015. The experiment was done for tomato variety Akshaya in rain shelter with 4 treatments of irrigation levels. The experiment was laid out in CRD with 3 replications. The main objectives of the study were to evaluate the performance of sensor based automated drip irrigation systems, scheduling irrigation for tomato based on the best performing drip automation system and to evaluate the cost economics of drip automation system with optimal irrigation scheduling. Irrigation was provided using sensors through drip automation system at 40 per cent, 50 per cent and 60 per cent moisture depletion levels (MDL) from the available moisture content. Control was irrigated at the rate of 2 l/plant/day. Crop growth parameters such as height of the plant, number of days to first flowering, number of days to initial budding, number of days to first harvest, root length and root dry weight were observed. During all the stages, plant height significantly varied in all treatments. All the parameters were found to be better in 50 per cent MDL treatment compared to other treatments. Yield parameters such as number of fruits and total yield were recorded. There was no significant difference in number of fruits per plant in all the treatments. Yield was significantly higher in 50 per cent MDL than that of other treatments. Water use efficiency was significantly different in all the treatments. WUE in T2 and T3 was on par which showed better performance than other treatments. The analysis of the data of soil moisture content at 2 and 6 hours after irrigation was monitored at distances of 0, 15 and 30 cm from the emitter laterally and at a depth of 0, 10, 20 and 30 cm from the surface. Soil moisture contour maps for the longitudinal section of the soil were plotted using computer software “Teraplot 1.3.02” version. The pattern was more uniform for T2 (50 per cent MDL) two hours after irrigation. Benefit cost (B/C) ratio for each treatment was calculated. The maximum benefit cost ratio of 2.57 was noted in T2. Hence it can be concluded that for tomato (Akshaya) grown in rain shelter, 50 per cent MDL can be fixed as the optimum level for scheduling irrigation. As 60 per cent moisture depletion also gave good yield and WUE on par with 50 per cent level, 60 per cent MDL can also be suggested for scheduling irrigation in water scarce areas.